Perbandingan Kebijakan Hukum terhadap Tanggung Jawab Transnasional Corporations atas Pelanggaran Hak Menikmati Lingkungan yang Sehat di Beberapa Negara - Sri Wartini; Jamaludin Ghafur (Jurnal Hukum IUS QUIA IUSTUM, 2015)
Most TNCs investing in developing countries control the exploitation of natural resources. However, the environmental protection standards applied by TNCs in the home state and the host state are not the same. The bad experiences occuring in some developing countries (Indonesia, India, Ecuador, and Nigeria) triggervarious policies to protect the right to enjoy a healthy environment. This study comprehensively analyzes: first, how is the legal policy of the responsibility of TNCs on the right protection to enjoy healthy environment in Indonesia, India, Ecuador, Nigeria and Finland? Second, what are the similarities and differences in its policymaking? This study is a qualitative research with normative and comparative juridical approach. The results of this study concluded that, first, the legal policies of developing countries towards the violation of TNCs responsibilities to enjoy a healthy environment have the same pattern, which is pretty mild in granting sanction, and prioritizing more on the economic growth rather than protecting the right to enjoy healthy environment. Second, the similar legal policy between these countries lies on the fact that they have recognized the right to enjoy healthy environment as a constitutional right and part of human rights. However, the implementation of the legal protection of the right to enjoy healthy environment differs from one country to another.